2015
DOI: 10.1542/peds.2014-3143
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Extremely Low Birth Weight Survivors in Their 30s

Abstract: OBJECTIVE: To determine the risk for psychiatric disorders among extremely low birth weight (ELBW) survivors in their early to mid-30s and to determine whether those born small for gestational age or those exposed to a full course of antenatal corticosteroids (ACS) were at particularly high risk.METHODS: A prospective, longitudinal, population-based cohort of 84 ELBW survivors and 90 normal birth weight (NBW) control participants born in Ontario, Canada from 1977 to 1982 were assessed by interviewers naive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
143
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 42 publications
9
143
1
3
Order By: Relevance
“…As an example of this is attention deficit/hyperactivity disorder, which has been documented to create a significant risk of mortality, psychiatric disorders, and morbidity well into adulthood [16]. In addition, some of the patients in our study were of extremely low birth weight and, as a consequence, were at higher risk for psychiatric disorders when reaching adulthood [17]. …”
Section: Discussionmentioning
confidence: 93%
“…As an example of this is attention deficit/hyperactivity disorder, which has been documented to create a significant risk of mortality, psychiatric disorders, and morbidity well into adulthood [16]. In addition, some of the patients in our study were of extremely low birth weight and, as a consequence, were at higher risk for psychiatric disorders when reaching adulthood [17]. …”
Section: Discussionmentioning
confidence: 93%
“…7 A recent study, which is the longest cohort study to date of extreme low-birth weight survivors, demonstrated that cases of babies born with a birth weight under 1000 g were more likely to exhibit a psychiatric problem than their normal birth weight counterparts. 16 However, Doppler status was not formally assessed within the methodology, probably because its routine use predated the starting date of the study.…”
Section: Discussionmentioning
confidence: 99%
“…This interview was complemented by additional modules from the MINI-Plus 33 which added lifetime disorders. Van Lieshout et al 25 previously reported the procedures for this sample. For both the YASR and MINI outcomes, a minimum prevalence threshold of 5 cases total (ELBW plus NBW) was required for a disorder to be included.…”
Section: Outcome: Psychiatric Disordersmentioning
confidence: 99%
“…20 The exposure of ELBW survivors to significant prenatal and postnatal adversity likely contributes to their increased vulnerability to the adverse psychiatric effects of peer victimization. [21][22][23][24][25] While recent evidence suggests that children born very preterm and who experience peer victimization may have elevated rates of emotional problems in childhood, it is not clear if these persist into adulthood. 26 In addition, it is not known if these problems are clinically significant as they have been typically measured by using screening questionnaires.…”
mentioning
confidence: 99%